2023
DOI: 10.3389/fneur.2023.1080331
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Intracranial lesions of cat-scratch disease mimicking an atypical meningioma

Abstract: ObjectivesCat-scratch disease (CSD) is an infectious disease caused by Bartonella henselae. The most typical symptom of patients with CSD is regional lymphadenopathy, while central nervous system lesions related to CSD are rare. Here, we present a case of an aged woman with CSD involving the dura mater with a manifestation similar to that of an atypical meningioma.MethodsThe patient was followed up by our neurosurgery and radiology teams. Clinical information was recorded, and the pre- and post-operation CT re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
(16 reference statements)
0
5
0
2
Order By: Relevance
“…3 The histopathologic findings of intracranial lesions obtained from previously reported patients with disseminated B. henselae infection showed microglial nodules and central stellate microabscesses. 5,6 The present case indicated that intracranial granulomatous lesions could occur in B. henselae infection. The intracranial lesions in our patient were incidentally detected on brain MRI performed to evaluate his cutaneous head masses.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…3 The histopathologic findings of intracranial lesions obtained from previously reported patients with disseminated B. henselae infection showed microglial nodules and central stellate microabscesses. 5,6 The present case indicated that intracranial granulomatous lesions could occur in B. henselae infection. The intracranial lesions in our patient were incidentally detected on brain MRI performed to evaluate his cutaneous head masses.…”
Section: Discussionmentioning
confidence: 50%
“…To our knowledge, 6 patients with B. henselae infection complicated with intracranial lesions, including nodules and abscesses, have been reported; 2 of these patients were children. 2,5,6,[10][11][12] Clinical symptoms and intracranial lesions in 4 adult cases were resolved using rifampicin in combination with doxycycline or sulfamethoxazole. 6,[10][11][12] One pediatric case improved spontaneously, whereas another patient who did not receive an appropriate antimicrobial therapy died before being diagnosed with B. henselae infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Атиповий перебіг захворювання буває у 5-20% пацієнтів віком 15-49 років та піком захорюванності з жовтня по січень [6]. Проявами захворювання є кон'юнктивіт Паріно (2-6%), нейроретиніт [21,22,23] та ураження центральної нервової системи (1-7%) [24,25,26].…”
unclassified